Identification of tick-borne pathogens using metagenomic analyses in H. longicornis feeding on humans in downtown Beijing - Jizhou Lv (BMC, 2021)
Abstract On August 14th, 2018, a Beijing resident living in Xicheng District found a female H. longicornis tick attached to the skin at the front of his upper shin. On examination, the patient was afebrile and appeared well. The species of the tick was identified through morphological characteristics and phylogenetic analysis based on cytochrome C oxidase subunit I. This H. longicornis tick was screened for tick-borne pathogens such as viruses, bacteria and parasites. RNA pathogens were screened by PCR and sequencing, while DNA pathogens were screened by metagenomic analyses. It was found that the tick was positive for the DNA sequences of zoonotic and animal pathogens such as A. phagocytophilum, Ehrlichia minasensis and C. burnetii. Considering the good health condition of the patient, we hypothesized that the pathogens originated from the tick specimen itself rather than host blood meal. For the first time, our study reveals the possible risk of transmission of tick-borne pathogens to human beings through tick bit in downtown Beijing. Further research is needed to screen for tick-borne pathogens among unfed ticks collected from central Beijing.